Flexible perovskite solar cell and preparation method thereof
By forming a parylene layer and stacked structure on the bearing substrate, combined with the laser peeling process, the problem of high production cost of flexible perovskite solar cells is solved, and performance improvement and preparation efficiency improvement are achieved.
Patent Information
- Application Number
- CN202411754240.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The existing flexible perovskite solar cells have high production costs, mainly due to the high cost of using flexible substrates.
A chemical vapor deposition process is used to form a parylene layer on the bearing substrate and a laminated structure is formed on its surface, including a perovskite layer and an electrode layer. The bearing substrate is peeled off from the parylene layer by a laser peeling process to obtain a flexible perovskite solar cell.
The preparation cost of flexible perovskite solar cells is reduced, its performance and preparation efficiency are improved, processes are reduced, and mechanical stability is enhanced.
Smart Images

Figure CN119584836A_ABST
Abstract
Description
Technical Field
[0001] The disclosed embodiments relate to the field of solar cell photovoltaic technology, and in particular to a flexible perovskite solar cell and a method for preparing the same. Background Art
[0002] As an emerging photovoltaic technology, flexible perovskite solar cells have attracted widespread attention due to their excellent photoelectric performance, good flexibility and bending, simple preparation process (such as spin coating, coating printing, roll-to-roll printing, etc.), and suitability for large-scale continuous production. They have shown wide application potential in scenarios such as wearable devices and portable power supplies, and are an important research direction in the field of solar cells. At present, the photoelectric conversion efficiency of flexible perovskite solar cells has exceeded 25%. However, the flexible substrates currently used are mainly polyethylene terephthalate (PET), polyethylene 2,6-naphthalate (PEN), polyethersulfone (PES) and polyimide (PI), which are relatively expensive, making the preparation cost of flexible perovskite solar cells in related technologies relatively high. Summary of the invention
[0003] The embodiments of the present disclosure provide a flexible perovskite solar cell and a method for preparing the same, which can at least reduce the preparation cost of the flexible perovskite solar cell and improve the performance and preparation efficiency of the flexible perovskite solar cell.
[0004] According to some embodiments of the present disclosure, on the one hand, the embodiments of the present disclosure provide a method for preparing a flexible perovskite solar cell, comprising: providing a carrier substrate; forming a polyparaxylene layer on the carrier substrate using a chemical vapor deposition process; forming a stacked structure on a surface of the polyparaxylene layer away from the carrier substrate, the stacked structure comprising at least a perovskite layer and a first electrode layer and a second electrode layer located on opposite sides of the perovskite layer, the first electrode layer being located between the polyparaxylene layer and the perovskite layer; after forming the stacked structure, performing a peeling process to peel the carrier substrate off the polyparaxylene layer.
[0005] In some embodiments, the steps of forming the polyparaxylene layer include: placing the supporting substrate on a carrier in the chamber of a chemical vapor deposition device; weighing 50g to 500g of polyparaxylene powder, and placing the polyparaxylene powder into a heating boat in the chamber; extracting the gas in the chamber so that the vacuum degree in the chamber meets a preset vacuum degree; heating the heating boat to a first temperature at a first heating rate, and keeping the heating boat at the first temperature for a first insulation time, the polyparaxylene undergoes a cracking reaction to form a gas monomer, and the gas monomer is deposited on the supporting substrate to form the polyparaxylene layer.
[0006] In some embodiments, the preset vacuum degree is 1×10 -3 Pa~1×10 -6 Pa, the first heating rate is 5°C / min to 30°C / min, the first temperature is 670°C to 710°C, and the first insulation time is 1h to 3h.
[0007] In some embodiments, the thickness of the polyparaxylene layer is 500 μm to 2 mm.
[0008] In some embodiments, a laser lift-off process is used to lift the carrier substrate off from the polyparaxylene layer. The process parameters of the laser lift-off process include: a laser wavelength of 200 nm to 400 nm, and a laser power of 2 W to 10 W.
[0009] In some embodiments, the process steps for forming the stacked structure include: forming the first electrode layer on the surface of the polyparaxylene layer facing away from the supporting substrate; forming a first charge transport layer on the surface of the first electrode layer facing away from the polyparaxylene layer; forming the perovskite layer on the surface of the first charge transport layer facing away from the first electrode layer; and forming a second electrode layer on the surface of the perovskite layer facing away from the first charge transport layer.
[0010] In some embodiments, after forming the perovskite layer and before forming the second electrode layer, it also includes: forming a second charge transport layer on the surface of the perovskite layer facing away from the polyparaxylene layer; the first charge transport layer is one of the electron transport layer and the hole transport layer, and the second charge transport layer is the other of the electron transport layer and the hole transport layer.
[0011] In some embodiments, the step of forming a first electrode layer includes: providing a first electrode target material, placing the supporting substrate including the polyparaxylene layer and the first electrode target material into a sputtering chamber of a magnetron sputtering apparatus, wherein the first electrode target material is used to form the first electrode layer; extracting gas from the sputtering chamber so that the vacuum degree in the sputtering chamber meets a preset vacuum degree; sputtering the first electrode target material using a DC sputtering method to form the first electrode layer on the surface of the polyparaxylene layer, wherein the sputtering power is 150W to 250W, and the sputtering time is 20min to 40min.
[0012] In some embodiments, after sputtering the first electrode target material to form the first electrode layer, the method also includes: extracting the gas in the sputtering chamber, the extraction time is 8 minutes to 12 minutes; providing a first charge transfer target material, and sputtering the first charge transfer target material by radio frequency sputtering to form a first charge transfer layer on the surface of the first electrode layer, and the sputtering power is 50W to 70W.
[0013] According to some embodiments of the present disclosure, on the other hand, the embodiments of the present disclosure further provide a flexible perovskite solar cell prepared by the preparation method of the above embodiments, including a polyparaxylene layer and a stacked structure, wherein the stacked structure is located on the surface of the polyparaxylene layer, and the stacked structure includes at least a perovskite layer and a first electrode layer and a second electrode layer located on opposite sides of the perovskite layer, wherein the first electrode layer is located between the polyparaxylene layer and the perovskite layer.
[0014] The technical solution provided by the embodiments of the present disclosure has at least the following advantages:
[0015] The technical solution of the method for preparing a flexible perovskite solar cell provided in the embodiment of the present disclosure includes: providing a carrier substrate; forming a polyparaxylene layer on the carrier substrate by a chemical vapor deposition process; forming a laminated structure on the surface of the polyparaxylene layer away from the carrier substrate, the laminated structure at least including a perovskite layer and a first electrode layer and a second electrode layer located on opposite sides of the perovskite layer; after forming the laminated structure, a peeling process is performed to peel the carrier substrate from the polyparaxylene layer. In the embodiment of the present disclosure, the polyparaxylene layer with a lower cost is used as the flexible substrate of the flexible perovskite solar cell, which can reduce the preparation cost of the flexible perovskite solar cell. In addition, the embodiment of the present disclosure adopts a chemical vapor deposition process to prepare the polyparaxylene layer, and the chemical vapor deposition process can convert solid reactants into gaseous reactants, so that the gaseous reactants react on the surface of the carrier substrate to form a film layer. The molecular energy of the gaseous reactants is high and the fluidity is strong. They can be evenly diffused and reacted on the surface of the carrier substrate, so that a polyparaxylene layer with good uniformity and high density can be prepared, which can improve the performance of the flexible perovskite solar cell. In addition, internal stress will be generated inside the film layer prepared by the chemical vapor deposition process. The polyparaxylene layer with excellent plasticity used in the embodiment of the present disclosure is used as a flexible substrate. The polyparaxylene layer can buffer and release these internal stresses through local plastic deformation, thereby eliminating the need to use an annealing process to remove the internal stress after the flexible substrate is prepared by the chemical vapor deposition process as in the related art. This can reduce the number of steps for preparing flexible perovskite solar cells, thereby improving the preparation efficiency of flexible perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] One or more embodiments are exemplarily illustrated by pictures in the corresponding drawings, and these exemplified descriptions do not constitute a limitation on the embodiments. Unless otherwise specified, the pictures in the drawings do not constitute a scale limitation. In order to more clearly illustrate the embodiments of the present disclosure or the technical solutions in the traditional technology, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 A schematic cross-sectional structure diagram of a flexible perovskite solar cell corresponding to a supporting substrate, a polyparaxylene layer and a laminated structure provided in the preparation method provided in an embodiment of the present disclosure;
[0018] Figure 2 A cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure;
[0019] Figure 3Another cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure;
[0020] Figure 4 A structural diagram of a formal flexible perovskite solar cell provided in an embodiment of the present disclosure;
[0021] Figure 5 A structural diagram of an inverted flexible perovskite solar cell provided in an embodiment of the present disclosure;
[0022] Figure 6 Another cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure;
[0023] Figure 7 Another cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure;
[0024] Figure 8 This is a cross-sectional SEM image of the flexible perovskite solar cell prepared in Example 1;
[0025] Fig. 9 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 1;
[0026] Fig.10 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 3;
[0027] Fig.11 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 7;
[0028] Fig.12 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 8;
[0029] Fig.13 This is a test diagram of the mechanical bending stability of the flexible perovskite solar cell prepared in Example 1;
[0030] Fig.14 This is a graph showing the mechanical bending stability test of the flexible perovskite solar cell prepared in Example 7. DETAILED DESCRIPTION
[0031] It can be seen from the background technology that the preparation cost of flexible perovskite solar cells in the related art is relatively high.
[0032] In the embodiment of the present disclosure, a low-cost polyparaxylene layer is used as a flexible substrate for a flexible perovskite solar cell, which can reduce the preparation cost of the flexible perovskite solar cell. In addition, the embodiment of the present disclosure adopts a chemical vapor deposition process to prepare the polyparaxylene layer, which can prepare a polyparaxylene layer with good uniformity and high density, and can improve the performance of the flexible perovskite solar cell. In addition, internal stress will be generated inside the film layer prepared by the chemical vapor deposition process. The polyparaxylene layer with excellent plasticity used in the embodiment of the present disclosure is used as a flexible substrate. The polyparaxylene layer can buffer and release these internal stresses through local plastic deformation, so there is no need to use an annealing process to remove the internal stress after preparing the flexible substrate by a chemical vapor deposition process as in the related art, which can reduce the process of preparing a flexible perovskite solar cell, and thus can improve the preparation efficiency of flexible perovskite solar cells.
[0033] The following will describe the various embodiments of the present disclosure in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present disclosure, many technical details are provided in order to enable the reader to better understand the present disclosure. However, even without these technical details and various changes and modifications based on the following embodiments, the technical solutions claimed in the present disclosure can be implemented.
[0034] Figure 1 A schematic cross-sectional structure diagram of a flexible perovskite solar cell corresponding to a supporting substrate, a polyparaxylene layer and a stacked structure is provided in the preparation method provided in an embodiment of the present disclosure.
[0035] refer to Figure 1 The preparation method of a flexible perovskite solar cell includes: providing a carrier substrate 100; forming a polyparaxylene layer 101 on the carrier substrate 100 using a chemical vapor deposition process; forming a laminated structure 102 on a surface of the polyparaxylene layer away from the carrier substrate, the laminated structure at least including a perovskite layer 112 and a first electrode layer 122 and a second electrode layer 132 located on opposite sides of the perovskite layer 112, and the first electrode layer 122 is located between the polyparaxylene layer 101 and the perovskite layer 112.
[0036] The carrier substrate 100 is used to provide support for the polyparaxylene layer 101 and the laminated structure 102 .
[0037] The carrier substrate 100 may be a rigid substrate such as a glass substrate, a metal substrate, or a ceramic substrate.
[0038] The polyparaxylene layer 101 can be formed on the surface of the supporting substrate 100 by chemical vapor deposition. The polyparaxylene layer 101 is used as a flexible substrate of the flexible perovskite solar cell to provide mechanical support for the laminated structure 102 and give the flexible perovskite solar cell light and flexible characteristics, thereby broadening the application scenarios of the flexible perovskite solar cell.
[0039] In some embodiments, before forming the polyparaxylene layer 101 on the carrier substrate 100, the process further includes: using a detergent to ultrasonically clean the carrier substrate 100, and drying the carrier substrate 100 after cleaning. Specifically, the rigid glass substrate is ultrasonically cleaned using a detergent, acetone, isopropyl alcohol, and deionized water in sequence; then, the cleaned carrier substrate 100 is dried.
[0040] In some embodiments, the step of forming the polyparaxylene layer 101 includes: placing a carrier substrate 100 on a carrier in a chamber of a chemical vapor deposition device; weighing 50g to 500g of polyparaxylene powder, for example, weighing 50g, 100g, 150g, 200g, 250g, 300g, 350g, 400g, 450g or 500g, and placing the polyparaxylene powder into a heating boat in the chamber; extracting gas in the chamber so that the vacuum degree in the chamber meets a preset vacuum degree; heating the heating boat to a first temperature at a first heating rate, and keeping the heating boat at the first temperature for a first insulation time, so that the polyparaxylene undergoes a cracking reaction and forms a gas monomer, and the gas monomer is deposited on the carrier substrate 100 to form the polyparaxylene layer 101.
[0041] In some embodiments, the preset vacuum degree is 1×10 -6 Pa~1×10 -3 Pa, for example 1×10 -6 Pa, 1×10 -5 Pa, 1×10 -4 Pa or 1×10 -3 Pa, etc., the first heating rate is 5°C / min to 30°C / min, such as 5°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min or 30°C / min, etc., the first temperature is 670°C to 710°C, such as 670°C, 680°C, 690°C, 700°C or 710°C, etc., and the first insulation time is 1h to 3h, such as 1h, 1.5h, 2h, 2.5h, or 3h. The process parameters for preparing the polyparaxylene layer 101 are within the above range, and a polyparaxylene layer 101 with good uniformity and high density can be prepared, thereby improving the performance of flexible perovskite solar cells.
[0042] In some embodiments, the thickness of the polyparaxylene layer 101 is 500 μm to 2 mm, for example, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1 mm, 1.5 mm or 2 mm, etc. The thickness of the polyparaxylene layer 101 within this range is relatively thin, and the polyparaxylene layer 101 has excellent flexibility and tensile strength. Therefore, when the polyparaxylene layer 101 is used as a flexible substrate of a flexible perovskite solar cell, the polyparaxylene layer 101 with a relatively thin thickness within the above range can provide a higher mechanical support force to the laminated structure 102, so that the overall thickness of the prepared flexible perovskite solar cell can be thinner, so that the flexible perovskite solar cell has broad prospects and potential in multiple application fields.
[0043] The gas monomer is an active para-xylene monomer. The gas monomer has high molecular energy and strong fluidity, and can diffuse and react evenly on the surface of the supporting substrate 100 to form a poly-para-xylene layer 101 with good uniformity and high density.
[0044] The laminate structure 102 is used to convert solar energy into electrical energy.
[0045] Figure 2 A cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure.
[0046] refer to Figure 2 In some embodiments, the process steps for forming the stacked structure 102 include: forming a first electrode layer 122 on a surface of the polyparaxylene layer 101 facing away from the supporting substrate 100; forming a first charge transport layer 142 on a surface of the first electrode layer 122 facing away from the polyparaxylene layer 101; forming a perovskite layer 112 on a surface of the first charge transport layer 142 facing away from the first electrode layer 122; and forming a second electrode layer 122 on a surface of the perovskite layer 112 facing away from the first charge transport layer 142.
[0047] The first electrode layer 122 is used to collect a type of carrier (electron or hole) generated by the perovskite layer 112 and conduct the carrier to an external circuit.
[0048] The material of the first electrode layer 122 may be a conductive material with good light transmittance, such as ITO (Indium Tin Oxide) or FTO (Fluorine-doped Tin Oxide). The good light transmittance of the first electrode layer 122 allows sunlight to pass through the first electrode layer 122 and reach the perovskite layer 112, thereby ensuring that the perovskite layer 112 effectively absorbs light.
[0049] In some embodiments, the step of forming the first electrode layer 122 includes: providing a first electrode target, placing the carrier substrate 100 including the polyparaxylene layer 101 and the first electrode target into a sputtering chamber of a magnetron sputtering apparatus, wherein the first electrode target is used to form the first electrode layer 122; extracting gas from the sputtering chamber so that the vacuum degree in the sputtering chamber meets a preset vacuum degree; sputtering the first electrode target by direct current sputtering to form the first electrode layer 122 on the surface of the polyparaxylene layer 101, wherein the preset vacuum degree is 1×10 -6 Pa~1×10 -3 Pa, for example 1×10 -6 Pa, 1×10 -5 Pa, 1×10 -4 Pa or 1×10 -3 Pa, etc., the sputtering power is 150W-250W, for example, 150W, 170W, 190W, 210W, 230W or 250W, and the sputtering time is 20min-40min, for example, 20min, 25min, 30min, 35min or 40min.
[0050] The first electrode target is used to form the first electrode layer 122. When the first electrode layer 122 is ITO, the first electrode target is an ITO target, and when the first electrode layer 122 is FTO, the first electrode target is an FTO target.
[0051] In the preparation method provided in the embodiment of the present disclosure, magnetron sputtering is used to prepare the first electrode layer 122. The atoms formed by sputtering the first electrode target have higher energy and can form a good bond with the polyparaxylene layer 101 when deposited on the surface of the polyparaxylene layer 101, so that the adhesion between the first electrode layer 122 and the polyparaxylene layer 101 is strong and not easy to fall off or peel off, which can improve the reliability of the flexible perovskite solar cell. The thin film prepared by magnetron sputtering has good uniformity and high density, which can improve the performance of the flexible perovskite solar cell.
[0052] The first charge transport layer 142 is used to transport a type of carrier (electron or hole) generated by the perovskite layer 112 to the first electrode layer 122. The first charge transport layer 142 is a hole transport layer or an electron transport layer.
[0053] The preparation process of the first charge transport layer 142 includes magnetron sputtering or spin coating.
[0054] In some embodiments, after the first electrode target is sputtered to form the first electrode layer 122, the process further includes: extracting the gas in the sputtering chamber for 8 to 12 minutes, for example, 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes; providing a first charge transport target, sputtering the first charge transport target by radio frequency sputtering to form a first charge transport layer 142 on the surface of the first electrode layer 122, and the sputtering power is 50W to 70W, for example, 50W, 55W, 60W, 65W or 70W. After the first electrode target is sputtered to form the first electrode layer 122, the first charge transport layer 142 is continuously formed by a magnetron sputtering process, that is, the first electrode layer 122 and the first charge transport layer 142 are continuously prepared by a magnetron sputtering process in the same magnetron sputtering instrument, which can avoid the equipment adjustment, sample transfer and other links in the process of different process conversion, thereby saving the preparation time of the flexible perovskite solar cell and improving the preparation efficiency of the flexible perovskite solar cell.
[0055] In some embodiments, the first charge transport layer 142 may be tin oxide. The step of forming the first charge transport layer 142 may include: mixing a tin oxide nanoparticle solution with deionized water to prepare a tin oxide solution, then spin coating the tin oxide solution on the surface of the first electrode layer 122 facing away from the polyparaxylene layer 101, adjusting the rotation speed of the supporting substrate 100 on which the first electrode layer 122 is deposited to 3000 rpm to 5000 rpm, for example, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, etc. / min or 5000 rpm, the rotation time is 20s to 40s, for example, 20s, 25s, 30s, 35s or 40s, and annealing at 60℃ to 80℃ (for example, 60℃, 65℃, 70℃ or 80℃) in air for 8min to 15min (for example, 8min, 10min, 12min, 13min or 15min) to form a first charge transport layer 142 with a thickness of 20nm to 40nm (for example, 20nm, 25nm, 30nm, 35nm or 40nm).
[0056] Wherein, the volume ratio of the tin oxide nanoparticle solution to deionized water may be 1:7 to 1:3.
[0057] In some embodiments, the first charge transport layer 142 may be nickel oxide, and the steps of forming the first charge transport layer 142 may include: dissolving nickel oxide nanoparticles in a solvent to prepare a 10 mg / ml to 20 mg / ml nickel oxide solution, then spin coating the tin oxide solution on the surface of the first electrode layer 122 away from the polyparaxylene layer 101, adjusting the rotation speed of the supporting substrate 100 deposited with the first electrode layer 122 to 3000 rpm to 4000 rpm, for example, 3000 rpm, 3200 rpm, 3500 rpm. , 3800 rpm or 4000 rpm, the rotation time is 20s to 40s, for example 20s, 25s, 30s, 35s or 40s, and annealing at 60℃ to 80℃ (for example 60℃, 65℃, 70℃ or 80℃) in air for 8min to 15min, (for example 8min, 10min, 12min, 13min or 15min) to form a first charge transport layer 142 with a thickness of 20nm to 40nm (for example 20nm, 25nm, 30nm, 35nm or 40nm).
[0058] The solvent for dissolving the nickel oxide nanoparticles may be a mixed solution of ultrapure water and isopropanol in a volume ratio of 3:1 to 5:1.
[0059] The perovskite layer 112 is used to absorb sunlight and generate carriers. The material of the perovskite layer 112 can be all-inorganic metal halide (such as CsSnBr3, CsPbBr3, etc.), organic inorganic metal halide (MAPbI3 or FAPbI3, etc.) or doped metal halide (such as Cs x FA 1-x PbI3 or CsPb x Sn 1-x I3, etc., where 0<x<1).
[0060] The process of forming the perovskite layer 112 may include a one-step spin coating method, a two-step spin coating method, a vacuum vapor deposition method, an evaporation method, a coating method, and the like.
[0061] In some embodiments, the perovskite layer 112 may be Cs x FA 1-xPbI3 (0<x<1), the step of forming the perovskite layer 112 may include: weighing a certain amount of CsI (cesium iodide) powder, FAI (methyl ether iodide) powder and PbI2 (lead iodide) powder; preparing a mixed solvent, and placing the weighed CsI powder, FAI powder and PbI2 powder in the mixed solvent; heating and stirring the mixed solvent at a temperature of 60℃~80℃ (for example, 60℃, 65℃, 70℃ or 80℃) for 40min~80min (for example, 40min, 50min, 60min, 70min or 80min) to fully dissolve the above powders in the mixed solvent to prepare 1mol / ml~3mol / ml (1mol / ml, 1.5mol / ml, 2mol / ml, 2.5mol / ml, 3mol / ml, 4mol / ml, 5mol / ml, 6mol / ml, 7mol / ml, 8mol / ml, 9mol / ml, 10mol / ml, 11mol / ml, 12mol / ml, 13mol / ml, 14mol / ml, 15mol / ml, 16mol / ml, 17mol / ml, 18mol / ml, 19mol / ml, 20mol / ml, 21mol / ml, 22mol / ml, 23mol / ml, 24mol / ml, 25mol / ml, 26mol / ml, 27mol / ml, 28mol / ml, 29mol / ml, 30mol / ml, 31mol / ml, 32mol / ml, 33mol / ml, 34mol / ml, 36mol / ml, 37mol / ml, 38mol / ml, 39mol / ml, 40mol / ml, 41mol / ml, 42mol / ml, 43mol / ml, mol / ml or 3mol / ml) of a perovskite precursor solution, placing a supporting substrate 100 deposited with a polyparaxylene layer 101, a first electrode layer 122 and a first charge layer on a sample platform of a spin coater, forming a perovskite layer 112 on a surface of the first charge transport layer 142 away from the polyparaxylene layer 101 by spin coating technology, quickly placing the spin-coated perovskite layer into a vacuum chamber for evacuation treatment, evacuating to 8Pa~12Pa (for example, 8Pa, 9Pa, 10Pa, 11Pa or 12Pa) within 25s~35s (for example, 25s, 28s, 30s, 33s or 35s), and maintaining it at 8Pa~12Pa for 40s~80s (for example, 40s, 50s, 60s, 70s or 80s). This is followed by annealing at 60° C. to 80° C. (eg, 60° C., 65° C., 70° C., or 80° C.) for 8 min to 12 min (eg, 8 min, 9 min, 10 min, 11 min, or 12 min).
[0062] Among the certain amount of CsI powder, FAI powder and PbI2 powder, the mass of CsI powder can be 20mg-60mg (for example, 20mg, 30mg, 40mg or 50mg), the mass of FAI powder can be 100mg-190mg (for example, 100mg, 120mg, 140mg, 160mg or 190mg), and the mass of PbI2 powder can be 300mg-600mg (for example, 300mg, 400mg, 450mg, 500mg or 600mg). The mixed solvent is a mixed solvent of DMF (Dimethylformamide) solvent and DMSO (Dimethyl sulfoxide) solvent, and the volume ratio of DMF to DMSO can be 3:1-5:1, such as 3:1, 4:1 or 5:1. The rotation speed of the supporting substrate 100 is set to 2000 rpm to 4000 rpm, for example, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm or 4000 rpm, and the rotation time is 20s to 40s, for example, 20s, 25s, 30s, 35s or 40s.
[0063] In some embodiments, the perovskite layer 112 may be Cs x FA 1-x PbI3 (0<x<1), the step of forming the perovskite layer 112 may include: placing a certain amount of CsI powder, FAI powder and PbI2 powder into three sintered boats respectively, placing the three sintered boats into the evaporation chamber of the evaporator, placing the supporting substrate 100 deposited with the polyparaxylene layer 101, the first electrode layer 122 and the first charge layer on the tray in the evaporation chamber, and depositing CsI powder, FAI powder and PbI2 powder in sequence to form a CsI film layer, a FAI film layer and a PbI2 film layer on the surface of the first charge transport layer 142 away from the polyparaxylene layer 101. After the deposition process is completed, the supporting substrate 100 is taken out from the evaporation chamber, and the supporting substrate 100 deposited with the CsI film layer, the FAI film layer and the PbI2 film layer is annealed at a temperature of 60°C to 80°C (for example, 60°C, 65°C, 70°C or 80°C) for 8min to 15min (for example, 8min, 10min, 12min, 13min or 15min) to allow the CsI film layer, the FAI film layer and the PbI2 film layer to fully react chemically to form a perovskite layer 112.
[0064] Among them, in a certain amount of CsI powder, FAI powder and PbI2 powder, the mass of CsI powder can be 1g to 4g (for example, 1g, 2g, 3g or 4g), the mass of FAI powder can be 2g to 8g (for example, 2g, 4g, 5g, 7g or 8g), the mass of PbI2 powder can be 2g to 8g (for example, 2g, 4g, 5g, 7g or 8g), and the deposition rate of CsI powder can be For example or The rate of depositing FAI powder can be For example or The rate of depositing PbI2 powder can be For example or The thickness of the CsI film layer formed by deposition can be 50nm to 150nm, for example, 50nm, 80nm, 100nm, 130nm or 150nm; the thickness of the FAI film layer formed by deposition can be 250nm to 350nm, for example, 250nm, 280nm, 300nm, 330nm or 350nm; the thickness of the PbI2 film layer formed by deposition can be 250nm to 350nm, for example, 250nm, 280nm, 300nm, 330nm or 350nm.
[0065] The second electrode layer 122 is used to collect a type of carrier (electron or hole) generated by the perovskite layer 112 and conduct the carrier to an external circuit. The polarity of the carrier collected by the second electrode layer 122 is opposite to the polarity of the carrier collected by the first electrode layer 122.
[0066] The second electrode layer 122 can be a metal electrode such as gold, silver, etc., or can be a carbon electrode.
[0067] In some embodiments, the first charge transport layer 142 may be an electron transport layer, the second electrode layer 122 may be a carbon electrode, and the flexible perovskite solar cell prepared by the preparation method may be a flexible carbon-based solar cell without a hole transport layer, and the step of forming the second electrode layer 122 may include: forming an initial carbon electrode by screen printing on the surface of the perovskite layer 112 away from the second electrode layer 122, and performing 4 to 6 annealing processes on a heating table to form a carbon electrode, wherein in each annealing process, the heating table temperature may be 60°C to 80°C, for example, 60°C, 65°C, 70°C or 80°C, and the heating time may be 8min to 15min, for example, 8min, 10min, 12min, 13min or 15min, and after the annealing is completed, wait for the heating table to cool to room temperature for the next annealing.
[0068] In some embodiments, the second electrode layer 122 may be a gold electrode, and the step of forming the second electrode layer 122 may include: forming a gold electrode with a thickness of 80 nm to 120 nm on a surface of the second electrode layer 122 away from the perovskite layer 112 by a thermal evaporation process.
[0069] Figure 3 Another cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure.
[0070] refer to Figure 3 In some embodiments, after forming the perovskite layer 112 and before forming the second electrode layer 122 , the method further includes: forming a second charge transport layer 152 on a surface of the perovskite layer 112 facing away from the polyparaxylene layer 101 .
[0071] The second charge transport layer 152 is used to transport a type of carrier (electron or hole) generated by the perovskite layer 112 to the second electrode layer 122. The polarity of the carriers transported by the second charge transport layer 152 is opposite to the polarity of the carriers transported by the first charge transport layer 142. The first charge transport layer 142 is one of the electron transport layer and the hole transport layer, and the second charge transport layer 152 is the other of the electron transport layer and the hole transport layer.
[0072] Figure 4 A structural diagram of a formal flexible perovskite solar cell provided in an embodiment of the present disclosure, Figure 5 A structural diagram of an inverted flexible perovskite solar cell provided in an embodiment of the present disclosure.
[0073] refer to Figure 4 When the first charge transport layer 142 is an electron transport layer and the second charge transport layer 152 is a hole transport layer, the flexible perovskite solar cell is a formal flexible perovskite solar cell. Figure 5 When the first charge transport layer 142 is a hole transport layer and the second charge transport layer 152 is an electron transport layer, the flexible perovskite solar cell is an inverted flexible perovskite solar cell.
[0074] The material of the second charge transport layer can be Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), PCBM ([6,6]-phenyl-C61-butyric acid methyl ester), or the like.
[0075] The second charge transport layer can be formed by spin coating, chemical vapor deposition, or the like.
[0076] Figure 6 Another cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure.
[0077] refer to Figure 6 In some embodiments, the first charge transport layer 142 is a hole transport layer, and the second charge transport layer 152 is an electron transport layer. After the electron transport layer is formed and before the second electrode layer 122 is formed, it also includes: forming a buffer layer 162 on the surface of the second charge transport layer 152 away from the perovskite layer 112; the method for forming the buffer layer 162 includes: dissolving BCP (Bathocuproine) in an isopropanol solution to form a buffer layer 162 precursor solution; spin coating the buffer layer 162 precursor solution on the surface of the electron transport layer away from the perovskite layer 112, and performing a first annealing treatment in a nitrogen atmosphere, the annealing temperature of the first annealing treatment is 60°C to 80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, and the annealing time of the first annealing treatment is 100s to 140s, for example, 100s, 110s, 120s, 130s or 140s. The bath copper layer is prepared by spin coating as the buffer layer 162. The preparation process is relatively simple and easy to operate, and the preparation efficiency of the flexible perovskite solar cell can be improved.
[0078] The buffer layer 162 can help electrons flow more smoothly from the electron transport layer to the second electrode layer 122, ensure efficient electron collection, improve the short-circuit current density and fill factor of the battery, and thus improve the photoelectric conversion efficiency of the battery. The buffer layer 162 can also adjust the energy level difference between the electron transport layer and the second electrode layer 122 to make them better match, reduce energy loss caused by energy level mismatch, and improve the performance of flexible perovskite solar cells.
[0079] Using a BCP layer with good electron transport properties as a buffer layer can improve the performance of flexible perovskite solar cells. BCP is soluble in common organic solvents and can be processed by a simple solution method, which can improve the preparation efficiency of flexible perovskite solar cells.
[0080] Figure 7 Another cross-sectional structure of a flexible perovskite solar cell prepared by the preparation method provided in an embodiment of the present disclosure.
[0081] refer to Figure 7 In some embodiments, the first charge transport layer 142 is a hole transport layer, and the second charge transport layer 152 is an electron transport layer. After forming the first charge transport layer 142 and before forming the perovskite layer 112, it may also include: forming a self-assembled monolayer 172 (SAMs, Self-Assembled Monolayers) on the surface of the first charge transport layer 142 away from the first electrode layer 122.
[0082] The self-assembled monolayer 172 can passivate defects at the interface between the vacancy transport layer and the perovskite layer 112, such as holes, dangling bonds, etc., which can reduce the number of recombination centers and improve the efficiency of flexible perovskite solar cells. It can also adjust the energy level difference between the hole transport layer and the perovskite layer 112, so that they are better matched, reduce energy loss caused by energy level mismatch, and improve the open circuit voltage of the flexible perovskite solar cell.
[0083] The material of the self-assembled monolayer 172 may be Me-4PACz, whose chemical formula is (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid), or phosphorylcholine chloride, long-chain thiol or selenium compound.
[0084] The self-assembled monolayer 172 can be formed by spin coating or vapor deposition.
[0085] Continue to refer Figure 1 After forming the stacked structure 102 , a peeling process is performed to peel the carrier substrate 100 from the polyparaxylene layer 101 .
[0086] In some embodiments, a laser lift-off process is used to lift the carrier substrate 100 off the polyparaxylene layer 101, and the process parameters of the laser lift-off process include: a laser wavelength of 200nm to 400nm, such as 200nm, 250nm, 300nm, 350nm or 400nm, and a laser power of 2W to 10W, such as 2W, 4W, 6W, 8W or 10W. The process parameters of the laser glass process within the above range will not cause physical damage to the polyparaxylene layer 101, which is conducive to the integrity of the polyparaxylene layer 101 and improves the quality and reliability of the flexible perovskite solar cell.
[0087] In some embodiments, the preparation method of the above-mentioned flexible perovskite solar cell is completed in an ambient temperature of 20°C to 30°C, for example, 20°C, 25°C or 30°C, and a humidity of less than 30%. The ambient temperature and humidity are within the above range, which helps to maintain the stability of the physical and chemical properties of the experimental raw materials and avoid unnecessary decomposition or conversion.
[0088] The advantages of the present application are further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application. Unless otherwise specified, the various parameters involved in this specification have general meanings known in the art and can be measured by methods known in the art. For example, it is possible to test according to the method provided in the examples of the present application. In addition, the preferred ranges and options of the various different parameters provided in the various preferred embodiments can be combined arbitrarily, and the various combinations obtained therefrom are all considered to be within the scope of the disclosure of the present application.
[0089] The flexible perovskite solar cells of Examples 1 to 10 were prepared as follows.
[0090] Example 1
[0091] Example 1 provides a method for preparing a flexible perovskite solar cell. In Example 1, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, the first charge transport layer (i.e., electron transport layer) is a SnO2 layer, and the perovskite layer is a Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (i.e., hole transport layer) is a Spiro-OMeTAD layer, the second electrode layer is a metal electrode Au, and the formal flexible perovskite solar cell prepared in Example 1 is prepared by the method of Example 1. The preparation method of Example 1 specifically includes the following steps:
[0092] (1) The rigid glass substrate is ultrasonically cleaned using a detergent, acetone, isopropyl alcohol, and deionized water in sequence; and then, the cleaned rigid glass substrate is dried.
[0093] (2) Weigh 100 g of polyparaxylene powder or granules and place them in a heating boat in the chamber of a chemical vapor deposition device. Place a rigid glass substrate on a stage in the chamber of the chemical vapor deposition device. Then close the chamber and start evacuating the vacuum until the vacuum drops to 10 -3 Pa, start heating polyparaxylene powder, raise the temperature to 690℃ at a rate of 10℃ / min, keep it at this temperature for 3 hours, let polyparaxylene undergo cracking reaction, and deposit on the rigid glass substrate to form a polyparaxylene layer. After the reaction is completed, the temperature is lowered to room temperature, and the cavity is opened to take samples.
[0094] (3) Place the rigid glass substrate with the polyparaxylene layer deposited on it into a magnetron sputtering instrument and evacuate the chamber to a vacuum of 1×10 -3 Pa, start depositing the ITO layer. Use DC sputtering, sputtering power of 200W, sputtering time of 30min, and the thickness formed is about 200nm. After the ITO layer is sputtered, continue to evacuate for 10 minutes, and then start sputtering the SnO2 layer. Use RF sputtering, power of 50W, sputtering time of 15min, and the thickness is about 20nm. After the sputtering of the ITO layer and the SnO2 layer is completed, open the cavity and take out the sample.
[0095] (4) 45 mg of CsI powder, 145 mg of FAI powder and 461 mg of PbI2 powder were dissolved in a DMF / DMSO mixed solvent (the volume ratio of DMF to DMSO was 4:1), heated and stirred at 70°C for 1 hour to prepare a 1.5 mol / ml perovskite precursor solution. A perovskite layer was prepared on the SnO2 layer by spin coating. During the spin coating process, the rotation speed of the rigid glass substrate with the SnO2 layer deposited was 3000 rpm and the rotation time was 30 seconds.
[0096] (5) The spin-coated perovskite layer was quickly placed in a vacuum chamber for evacuation, evacuated to 10 Pa in 30 seconds, and maintained at 10 Pa for 1 minute. It was then annealed at 70° C. for 10 minutes.
[0097] (6) Dissolve 73.2 mg of Spiro-OMeTAD in 1 ml of chlorobenzene solution to prepare a Spiro-OMeTAD solution. Dissolve 520 mg of lithium bis(trifluoromethanesulfonyl)imide in 1 ml of anhydrous acetonitrile solution to obtain a lithium bis(trifluoromethanesulfonyl)imide solution, and add 17.6 μl of lithium bis(trifluoromethanesulfonyl)imide solution and 28.8 μL of TBP (Tributylphosphate) solution to the above Spiro-OMeTAD solution to prepare a hole transport layer precursor solution. Spin-coat the hole transport layer precursor solution on the perovskite film to prepare a hole transport layer with a thickness of 80 nm.
[0098] (7) The thin film prepared above is placed in an evaporation chamber, and a metal electrode Au is evaporated on the hole transport layer by a thermal evaporation process with a thickness of 100 nm to obtain an initial flexible perovskite solar cell structure.
[0099] (8) The initial flexible perovskite solar cell structure prepared above is placed in a laser processing device, and a 365nm ultraviolet picosecond laser is used to process the four sides of the rigid glass substrate (laser power is 5W) to separate the polyparaxylene layer from the rigid glass substrate, thereby obtaining a formal flexible perovskite solar cell.
[0100] Example 2
[0101] Example 2 provides a method for preparing a flexible perovskite solar cell. In Example 2, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, the first charge transport layer (i.e., the electron transport layer) is a SnO2 layer, and the perovskite layer is a Cs 0.1 FA 0.9PbI3 layer, the second charge transport layer (ie, hole transport layer) is a Spiro-OMeTAD layer, and the second electrode layer is a metal electrode Au. The formal flexible perovskite solar cell prepared in Example 2 is obtained.
[0102] The preparation method of Example 2 is substantially the same as that of Example 1, except that Example 2 uses spin coating to prepare the SnO2 layer, while Example 1 uses magnetron sputtering to prepare the SnO2 layer.
[0103] The steps of preparing the SnO2 layer in Example 2 include: mixing a SnO2 nanoparticle solution and deionized water in a volume ratio of 1:5 to prepare a SnO2 solution, and then spin-coating the SnO2 solution on the surface of the ITO layer facing away from the polyparaxylene layer, wherein the rotation speed of the rigid glass substrate deposited with the ITO layer is adjusted to 4000 rpm, the rotation time is 30 seconds, and annealing is carried out in air at 70°C for 10 minutes to form a SnO2 layer with a thickness of 30 nm.
[0104] Example 3
[0105] Example 3 provides a method for preparing a flexible perovskite solar cell. In Example 3, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, the first charge transport layer (i.e., the electron transport layer) is a SnO2 layer, and the perovskite layer is a Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (ie, hole transport layer) is a Spiro-OMeTAD layer, and the second electrode layer is a metal electrode Au. The formal flexible perovskite solar cell prepared in Example 3 is obtained.
[0106] The preparation method of Example 3 is basically the same as that of Example 1, except that Example 3 uses a vapor deposition method to prepare Cs 0.1 FA 0.9 PbI3 layer, while Example 1 uses spin coating to prepare Cs 0.1 FA 0.9 PbI3 layer.
[0107] Example 3 Preparation of Cs by Evaporation 0.1 FA 0.9 The steps of forming the PbI3 layer include: weighing 2g of CsI powder, 5g of FAI powder and 5g of PbI2 powder, respectively placing them into three sintered boats in the evaporation chamber of the evaporation apparatus, and placing the rigid glass substrate with the ITO layer, SnO2 layer and polyparaxylene layer deposited on the tray in the evaporation chamber for evaporation. CsI powder, FAI powder and PbI2 powder are deposited in sequence, and the deposition rates are respectively and The thickness of the deposited CsI film layer, FAI film layer and PbI2 film layer are 10nm, 300nm and 300nm respectively. After the deposition is completed, the cavity is opened for sampling, and then annealed at 70℃ for 10min to form Cs 0.1 FA 0.9 PbI3 layer.
[0108] Example 4
[0109] Example 4 provides a method for preparing a flexible perovskite solar cell. In Example 4, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, the first charge transport layer (i.e., the electron transport layer) is a SnO2 layer, and the perovskite layer is a Cs 0.1 FA 0.9 The PbI3 layer, the second electrode layer is a carbon electrode, and the carbon-based formal flexible perovskite solar cell without a hole transport layer prepared in Example 4 specifically includes the following steps:
[0110] (1) The rigid glass substrate is ultrasonically cleaned using a detergent, acetone, isopropyl alcohol, and deionized water in sequence; and then, the cleaned rigid glass substrate is dried.
[0111] (2) Weigh 100 g of polyparaxylene powder or granules and place them in a heating boat in the chamber of a chemical vapor deposition device. Place a rigid glass substrate on a stage in the chamber of the chemical vapor deposition device. Then close the chamber and start evacuating the vacuum until the vacuum drops to 10 -3 Pa, start heating polyparaxylene powder, raise the temperature to 690℃ at a rate of 10℃ / min, keep it at this temperature for 3 hours, let polyparaxylene undergo cracking reaction, and deposit on the rigid glass substrate to form a polyparaxylene layer. After the reaction is completed, the temperature is lowered to room temperature, and the cavity is opened to take samples.
[0112] (3) Place the rigid glass substrate with the polyparaxylene layer deposited on it into a magnetron sputtering instrument and evacuate the chamber to a vacuum of 1×10 -3 Pa, start depositing the ITO layer. Use DC sputtering, sputtering power of 200W, sputtering time of 30min, and the thickness formed is about 200nm. After the ITO layer is sputtered, continue to evacuate for 10 minutes, and then start sputtering the SnO2 layer. Use RF sputtering, power of 50W, sputtering time of 15min, and the thickness is about 20nm. After the sputtering of the ITO layer and the SnO2 layer is completed, open the cavity and take out the sample.
[0113] (4) Weigh 2 g of CsI powder, 5 g of FAI powder, and 5 g of PbI2 powder, and place them in three sintered boats in the evaporation chamber of the evaporation apparatus, respectively. Place the rigid glass substrate with the ITO layer, SnO2 layer, and polyparaxylene layer deposited on the tray in the evaporation chamber for evaporation. Deposit CsI powder, FAI powder, and PbI2 powder in sequence, with deposition rates of and The thickness of the deposited CsI film layer, FAI film layer and PbI2 film layer are 10nm, 300nm and 300nm respectively. After the deposition is completed, the cavity is opened for sampling, and then annealed at 70℃ for 10min to form Cs 0.1 FA 0.9 PbI3 layer.
[0114] (5) The film prepared above was placed in a doctor blade coating apparatus and printed on Cs 0.1 FA 0.9 An initial carbon electrode is printed on the PbI3 layer, and an annealing process is carried out on a heating table (annealing temperature is 70°C, annealing time is 10 minutes), and then it is cooled to room temperature and placed on the heating table for the next annealing process (annealing process is cycled 5 times) to obtain a carbon-based perovskite solar cell.
[0115] (6) The carbon-based perovskite solar cell prepared above is placed in a laser processing device, and a 365nm ultraviolet picosecond laser is used to process the four sides of the glass substrate (power 5W) to achieve the peeling and separation of polyparaxylene from the rigid glass substrate, thereby obtaining a carbon-based flexible perovskite solar cell with a formal structure and no hole transport layer.
[0116] Example 5
[0117] Example 5 provides a method for preparing a flexible perovskite solar cell. In Example 5, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, and the first charge transport layer (i.e., the hole transport layer) is NiO y (nickel oxide) layer, the perovskite layer is Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (i.e., electron transport layer) is a PCBM layer, the buffer layer is a BCP layer, and the second electrode layer is a metal electrode Au. The inverted flexible perovskite solar cell prepared in Example 5 specifically includes the following steps:
[0118] (1) The rigid glass substrate is ultrasonically cleaned using a detergent, acetone, isopropyl alcohol, and deionized water in sequence; and then, the cleaned rigid glass substrate is dried.
[0119] (2) Weigh 100 g of polyparaxylene powder or granules and place them in a heating boat in the chamber of a chemical vapor deposition device. Place a rigid glass substrate on a stage in the chamber of the chemical vapor deposition device. Then close the chamber and start evacuating the vacuum until the vacuum drops to 10 -3 Pa, start heating polyparaxylene powder, raise the temperature to 690℃ at a rate of 10℃ / min, keep it at this temperature for 3 hours, let polyparaxylene undergo cracking reaction, and deposit on the rigid glass substrate to form a polyparaxylene layer. After the reaction is completed, the temperature is lowered to room temperature, and the cavity is opened to take samples.
[0120] (3) Place the rigid glass substrate with the polyparaxylene layer deposited on it into a magnetron sputtering instrument and evacuate the chamber to a vacuum of 1×10 -3 Pa, and then the ITO layer was deposited. DC sputtering was used, with a sputtering power of 200 W and a sputtering time of 30 min to form an ITO layer with a thickness of about 200 nm. After the ITO layer was sputtered, the vacuum was continuously pumped for 10 minutes, and then NiO was sputtered. y The ITO layer and NiO layer are connected by RF sputtering with a power of 60W and a sputtering time of 20min, and the thickness is about 20nm. y After the layer sputtering is completed, the chamber is opened and the sample is taken out.
[0121] (4) 45 mg of CsI powder, 145 mg of FAI powder and 461 mg of PbI2 powder were dissolved in a DMF / DMSO mixed solvent (the volume ratio of DMF to DMSO was 4:1), heated and stirred at 70°C for 1 hour to prepare a 1.5 mol / ml perovskite precursor solution. A perovskite layer was prepared on the SnO2 layer by spin coating. During the spin coating process, the rotation speed of the rigid glass substrate with the SnO2 layer deposited was 3000 rpm and the rotation time was 30 seconds.
[0122] (5) The spin-coated perovskite layer was quickly placed in a vacuum chamber for evacuation, evacuated to 10 Pa in 30 seconds, and maintained at 10 Pa for 1 minute. It was then annealed at 70° C. for 10 minutes.
[0123] (6) 50 mg of PCBM was dissolved in 2 ml of o-dichlorobenzene to prepare an electron transport layer precursor solution. The electron transport layer precursor solution was spin-coated on the perovskite layer and annealed at 70° C. for 5 minutes in nitrogen to prepare an electron transport layer with a thickness of 50 nm.
[0124] (7) 20 mg of BCP was dissolved in 2 mL of isopropanol to prepare a buffer layer precursor solution. The buffer layer precursor solution was spin-coated on the electron transport layer and annealed at 70° C. for 2 minutes in nitrogen to prepare a buffer layer with a thickness of 30 nm.
[0125] (8) The thin film prepared above was placed in an evaporation chamber, and a metal electrode Au was evaporated on the hole transport layer by a thermal evaporation process with a thickness of 100 nm to obtain a perovskite solar cell.
[0126] (9) The initial flexible perovskite solar cell structure prepared above is placed in a laser processing equipment, and a 365nm ultraviolet picosecond laser is used to process the four sides of the rigid glass substrate (laser power is 5W) to separate the polyparaxylene layer from the rigid glass substrate, thereby obtaining an inverted flexible perovskite solar cell.
[0127] Example 6
[0128] Example 6 provides a method for preparing a flexible perovskite solar cell. In Example 6, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, and the first charge transport layer (i.e., the hole transport layer) is NiO y layer, the perovskite layer is Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (ie, electron transport layer) is a PCBM layer, the buffer layer is a BCP layer, and the second electrode layer is a metal electrode Au. The inverted flexible perovskite solar cell prepared in Example 6 is obtained.
[0129] The preparation method of Example 6 is basically the same as that of Example 5, except that the spin coating method is used to prepare NiO y Layer, while Example 5 uses magnetron sputtering to prepare NiO y layer.
[0130] Example 6 Preparation of NiO by spin coating y The steps of layering include: y The nanoparticles were dissolved in a solvent (ultrapure water and isopropanol in a volume ratio of 4:1) to prepare 15 mg / ml NiO y solution, and then NiO y The solution was spin coated on the surface of the ITO layer facing away from the polyparaxylene layer, wherein the rotation speed of the polyparaxylene layer deposited with the ITO layer was set to 3500 rpm, the rotation time was 30 seconds, and annealed at 70°C in air for 10 minutes to prepare a hole transport layer with a thickness of 30 nm.
[0131] Example 7
[0132] Example 7 provides a method for preparing a flexible perovskite solar cell. In Example 7, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, and the first charge transport layer (i.e., the hole transport layer) is NiO y layer, the self-assembled monolayer is Me-4PACz layer, and the perovskite layer is Cs 0.1 FA0.9 PbI3 layer, the second charge transport layer (ie, electron transport layer) is a PCBM layer, the buffer layer is a BCP layer, and the second electrode layer is a metal electrode Au. The inverted flexible perovskite solar cell prepared in Example 7 is obtained.
[0133] The preparation method of Example 7 is substantially the same as that of Example 6, except that in Example 7, when forming NiO y After the formation of Cs 0.1 FA 0.9 Before the PbI3 layer, NiO y An assembled monolayer (ie, Me-4PACz layer) is formed on the surface facing away from the ITO layer.
[0134] The steps of forming the Me-4PACz layer include: dissolving Me-4PACz in an ethanol solution to form a precursor solution with a concentration of 1 mg / ml, and spin coating the precursor solution on the NiO y A layer of Me-4PACz is formed on the surface of the layer away from the ITO layer. y The rigid glass substrate of the layer was rotated at a speed of 3000 rpm for 60 seconds.
[0135] Example 8
[0136] Example 8 provides a method for preparing a flexible perovskite solar cell. In Example 8, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, and the first charge transport layer (i.e., the hole transport layer) is NiO y layer, the self-assembled monolayer is Me-4PACz, and the perovskite layer is Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (ie, electron transport layer) is a PCBM layer, the buffer layer is a BCP layer, and the second electrode layer is a metal electrode Au. The inverted flexible perovskite solar cell prepared in Example 8 is obtained.
[0137] The preparation method of Example 8 is basically the same as that of Example 7, except that in Example 8, NiO is prepared by magnetron sputtering. y layer, while Example 7 uses spin coating to prepare NiO y layer.
[0138] Preparation of NiO by magnetron sputtering y The steps of the layer include: after the ITO layer is sputtered, continue to evacuate for 10 minutes, and then start sputtering NiO y The ITO layer and NiO layer are connected by RF sputtering with a power of 60W and a sputtering time of 20min, and the thickness is about 20nm. y After the layer sputtering is completed, the chamber is opened and the sample is taken out.
[0139] Example 9
[0140] Example 9 provides a method for preparing a flexible perovskite solar cell. In Example 9, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, the first charge transport layer (i.e., the electron transport layer) is a SnO2 layer, and the perovskite layer is a Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (i.e., hole transport layer) is a Spiro-OMeTAD layer, the second electrode layer is a metal electrode Au, and the formal flexible perovskite solar cell prepared in Example 9 is prepared by the method of Example 9. The preparation method of Example 9 specifically includes the following steps:
[0141] The preparation method of Example 9 is basically the same as the preparation method of Example 1, except that in Example 9, the process parameters of the chemical vapor deposition process are different from the process parameters of the chemical vapor deposition process in Example 1. In Example 9, the polyparaxylene powder is heated to 670°C at 5°C / min, while in Example 1, the polyparaxylene powder is heated to 690°C at 10°C / min.
[0142] Specifically, the steps of preparing the polyparaxylene layer in Example 9 include: weighing 100g of polyparaxylene powder or particles, placing it in a heating boat in the chamber of the chemical vapor deposition equipment, placing the rigid glass substrate on the stage in the chamber of the chemical vapor deposition equipment. Then, the chamber is closed and vacuum is started. When the vacuum degree drops to 10 -3 Pa, start heating polyparaxylene powder, raise the temperature to 670℃ at a rate of 5℃ / min, keep it at this temperature for 3 hours, let polyparaxylene undergo cracking reaction, and deposit on the rigid glass substrate to form a polyparaxylene layer. After the reaction is completed, the temperature is lowered to room temperature, and the cavity is opened to take samples.
[0143] Example 10
[0144] Example 10 provides a method for preparing a flexible perovskite solar cell. In Example 10, the supporting substrate is a rigid glass substrate, the first electrode layer is an ITO layer, the first charge transport layer (i.e., the electron transport layer) is a SnO2 layer, and the perovskite layer is a Cs 0.1 FA 0.9 PbI3 layer, the second charge transport layer (i.e., hole transport layer) is a Spiro-OMeTAD layer, the second electrode layer is a metal electrode Au, and the formal flexible perovskite solar cell prepared in Example 9 is obtained. The preparation method of Example 10 specifically includes the following steps:
[0145] The preparation method of Example 10 is basically the same as the preparation method of Example 1, except that in Example 10, the process parameters of the chemical vapor deposition process are different from the process parameters of the chemical vapor deposition process in Example 1. In Example 9, the polyparaxylene powder is heated to 710°C at 30°C / min, while in Example 1, the polyparaxylene powder is heated to 690°C at 10°C / min.
[0146] Specifically, the steps of preparing the polyparaxylene layer in Example 10 include: weighing 100g of polyparaxylene powder or particles, placing it in a heating boat in the chamber of a chemical vapor deposition device, placing a rigid glass substrate on a stage in the chamber of the chemical vapor deposition device. Then, the chamber is closed and vacuum is started. When the vacuum degree drops to 10 -3 Pa, start heating polyparaxylene powder, raise the temperature to 710℃ at a rate of 30℃ / min, keep it at this temperature for 3 hours, let polyparaxylene undergo cracking reaction, and deposit on the rigid glass substrate to form a polyparaxylene layer. After the reaction is completed, the temperature is lowered to room temperature, and the cavity is opened to take samples.
[0147] Figure 8 This is a cross-sectional SEM (Scanning Electron Microscope) image of the flexible perovskite solar cell prepared in Example 1.
[0148] refer to Figure 8 It can be seen that the interfaces between the film layers in the flexible perovskite solar cell prepared in Example 1 are relatively flat and smooth, which is conducive to the transmission of carriers in the flexible perovskite solar cell, so that the flexible perovskite solar cell can have excellent performance.
[0149] Fig. 9 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 1; Fig.10 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 3; Fig.11 This is an efficiency curve diagram of the flexible perovskite solar cell prepared in Example 7; Fig.12 This is the efficiency curve of the flexible perovskite solar cell prepared in Example 8.
[0150] Table 1 shows the efficiency test results of the flexible perovskite solar cells prepared in Examples 1 to 10.
[0151] Table 1
[0152]
[0153]
[0154] Among them, Voc (Open-Circuit Voltage) in Table 1 is the open-circuit voltage of the flexible perovskite solar cell, Jsc (Short-Circuit Current Density) is the short-circuit current density of the flexible perovskite solar cell, FF (Fill Factor) is the fill factor of the flexible perovskite solar cell, and PCE (Power Conversion Efficiency) is the photoelectric conversion efficiency of the flexible perovskite solar cell.
[0155] Refer to Table 1 and Figures 9 to 12 , the PCE of the flexible perovskite solar cells prepared in Examples 1 to 10 are all higher than 14%, which can indicate that the flexible perovskite solar cells prepared by using the polyparaxylene layer formed by the chemical vapor deposition process as a flexible substrate can have excellent photoelectric performance. And the polyparaxylene layer formed by the chemical vapor deposition process is used as a flexible substrate. Whether the formal flexible perovskite solar cell, the inverted flexible perovskite solar cell, or the carbon-based hole-free formal flexible perovskite solar cell is prepared, the first charge transport layer is prepared by spin coating or magnetron sputtering, and the perovskite layer is prepared by spin coating or evaporation. A high photoelectric conversion efficiency can be achieved, which indicates that the method of using the polyparaxylene layer as a flexible substrate to prepare a flexible perovskite solar cell is feasible. In other words, the polyparaxylene layer formed by the chemical vapor deposition process shows excellent adaptability as a flexible substrate and can be adapted to flexible perovskite solar cells of different structures.
[0156] Fig.13 This is a test diagram of the mechanical bending stability of the flexible perovskite solar cell prepared in Example 1. Fig.14 This is a graph showing the mechanical bending stability test of the flexible perovskite solar cell prepared in Example 7.
[0157] Table 2 shows the mechanical bending stability results of the flexible perovskite solar cells prepared in Examples 1 to 10.
[0158] Table 2
[0159]
[0160]
[0161] Among them, the PCE retention rate in Table 2 is the ratio of the PCE after bending for a corresponding number of cycles to the initial PCE without bending.
[0162] Refer to Table 2 and Fig.13 and Fig.14The flexible perovskite solar cells prepared in Examples 1 to 10 can have a PCE retention rate of 0.8 after mechanical bending 350 times or more, which can indicate that the flexible perovskite solar cells prepared by using the polyparaxylene layer formed by the chemical vapor deposition process as a flexible substrate can have good mechanical stability.
[0163] With reference to Table 1 and Table 2, the PCE of the flexible perovskite solar cells prepared in Example 9 and Example 10 are slightly lower than the PCE of the flexible perovskite solar cell prepared in Example 1. When the PCE retention rate is the same, the number of bending cycles of the flexible perovskite solar cells prepared in Example 9 and Example 10 are less than the number of bending cycles of the flexible perovskite solar cell prepared in Example 1, that is, the mechanical stability of the flexible perovskite solar cells prepared in Example 9 and Example 10 is weaker than that of the flexible perovskite solar cell prepared in Example 1, while in Example 9, the number of bending cycles of the flexible perovskite solar cells prepared in Example 1 is less than that of the flexible perovskite solar cell prepared in Example 1. The difference between Example 10 and Example 1 is that the process parameters for preparing the polyparaxylene layer are different. Specifically, the heating rate and heating temperature of heating the polyparaxylene powder in Example 9 are lower than the heating rate and heating temperature of heating the polyparaxylene powder in Example 1, and the heating rate and heating temperature of Example 10 are higher than the heating rate and heating temperature of heating the polyparaxylene powder in Example 1. This shows that the performance of the polyparaxylene layer prepared by the process parameters of the chemical vapor deposition process in Example 1 is better, so that the flexible perovskite solar cell prepared on this basis has better photoelectric conversion efficiency and mechanical stability.
[0164] In the above-mentioned method for preparing a flexible perovskite solar cell, a low-cost polyparaxylene layer is used as a flexible substrate for a flexible perovskite solar cell, which can reduce the preparation cost of a flexible perovskite solar cell. In addition, the embodiment of the present disclosure adopts a chemical vapor deposition process to prepare a polyparaxylene layer to prepare a polyparaxylene layer with good uniformity and high density, which can improve the performance of a flexible perovskite solar cell. In addition, internal stress will be generated inside the film layer prepared by the chemical vapor deposition process. The polyparaxylene layer with excellent plasticity used in the embodiment of the present disclosure is used as a flexible substrate. The polyparaxylene layer can buffer and release these internal stresses through local plastic deformation, so there is no need to use an annealing process to remove the internal stress after preparing a flexible substrate by a chemical vapor deposition process as in the related art, which can reduce the process of preparing a flexible perovskite solar cell, and thus improve the preparation efficiency of a flexible perovskite solar cell.
[0165] Correspondingly, another embodiment of the present disclosure further provides a flexible perovskite solar cell prepared by the preparation method of any of the above embodiments. For the parts that are the same or corresponding to the previous embodiment, reference can be made to the corresponding description of the previous embodiment, and will not be described in detail below.
[0166] refer to Figure 2 The flexible perovskite solar cell includes: a polyparaxylene layer 101 and a stacked structure 102, wherein the stacked structure 102 is located on the surface of the polyparaxylene layer 101, and the stacked structure 102 includes at least a perovskite layer 112 and a first electrode layer 122 and a second electrode layer 122 located on opposite sides of the perovskite layer 112, wherein the first electrode layer 122 is located between the polyparaxylene layer 101 and the perovskite layer 112.
[0167] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for realizing the present disclosure, and in practical applications, various changes can be made to them in form and details without departing from the spirit and scope of the present disclosure. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present disclosure, so the protection scope of the present disclosure shall be based on the scope defined in the claims.
Claims
1. A method for preparing a flexible perovskite solar cell, characterized in that: include: providing a carrier substrate; Forming a polyparaxylene layer on the carrier substrate by using a chemical vapor deposition process; Forming a laminated structure on a surface of the polyparaxylene layer away from the supporting substrate, the laminated structure comprising at least a perovskite layer and a first electrode layer and a second electrode layer located on opposite sides of the perovskite layer, wherein the first electrode layer is located between the polyparaxylene layer and the perovskite layer; After the stacked structure is formed, a peeling process is performed to peel the carrier substrate from the polyparaxylene layer.
2. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: The steps of forming the polyparaxylene layer include: Placing the carrier substrate on a stage in a chamber of a chemical vapor deposition device; Weighing 50 g to 500 g of polyparaxylene powder, and placing the polyparaxylene powder into the heating boat in the cavity; Extracting gas from the cavity so that the vacuum degree in the cavity meets a preset vacuum degree; The heating boat is heated to a first temperature at a first heating rate, and the heating boat is kept at the first temperature for a first holding time, the polyparaxylene powder undergoes a cracking reaction and forms a gas monomer, and the gas monomer is deposited on the supporting substrate to form the polyparaxylene layer.
3. The method for preparing a flexible perovskite solar cell according to claim 2, characterized in that: The preset vacuum degree is 1×10 -6 Pa~1×10 -3 Pa, the first heating rate is 5°C / min-30°C / min, the first temperature is 670°C-710°C, and the first insulation time is 1h-3h.
4. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: The thickness of the polyparaxylene layer is 500 μm to 2 mm.
5. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: A laser stripping process is used to strip the carrier substrate from the polyparaxylene layer. The process parameters of the laser stripping process include: a laser wavelength of 200nm to 400nm, and a laser power of 2W to 10W.
6. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: The process steps for forming the stacked structure include: forming the first electrode layer on a surface of the polyparaxylene layer facing away from the supporting substrate; forming a first charge transport layer on a surface of the first electrode layer facing away from the polyparaxylene layer; forming the perovskite layer on a surface of the first charge transport layer facing away from the first electrode layer; A second electrode layer is formed on a surface of the perovskite layer facing away from the first charge transport layer.
7. The method for preparing a flexible perovskite solar cell according to claim 6, characterized in that: After forming the perovskite layer and before forming the second electrode layer, the method further includes: forming a second charge transport layer on a surface of the perovskite layer facing away from the polyparaxylene layer; The first charge transport layer is one of an electron transport layer and a hole transport layer, and the second charge transport layer is the other of the electron transport layer and the hole transport layer.
8. The method for preparing a flexible perovskite solar cell according to claim 6, characterized in that: The step of forming the first electrode layer comprises: Providing a first electrode target material, placing the carrier substrate including the polyparaxylene layer and the first electrode target material into a sputtering chamber of a magnetron sputtering apparatus, wherein the first electrode target material is used to form the first electrode layer; Extracting gas from the sputtering chamber so that the vacuum degree in the sputtering chamber meets a preset vacuum degree; The first electrode target material is sputtered by direct current sputtering to form the first electrode layer on the surface of the polyparaxylene layer, wherein the preset vacuum degree is 1×10 -6 Pa~1×10 -3 Pa, the sputtering power is 150W~250W, and the sputtering time is 20min~40min.
9. The method for preparing a flexible perovskite solar cell according to claim 8, characterized in that: After sputtering the first electrode target to form the first electrode layer, the method further includes: Extracting the gas in the sputtering chamber for 8 to 12 minutes; A first charge transfer target material is provided, and the first charge transfer target material is sputtered by radio frequency sputtering to form a first charge transfer layer on the surface of the first electrode layer, and the sputtering power is 50W to 70W.
10. A flexible perovskite solar cell prepared by the method for preparing a flexible perovskite solar cell according to any one of claims 1 to 9, characterized in that: include: A polyparaxylene layer and a stacked structure, wherein the stacked structure is located on the surface of the polyparaxylene layer, and the stacked structure at least includes a perovskite layer and a first electrode layer and a second electrode layer located on opposite sides of the perovskite layer, wherein the first electrode layer is located between the polyparaxylene layer and the perovskite layer.